Study of CO2 Adsorption on Chemically Modified Activated Carbon With Nitric Acid and Ammonium Aqueous - Giraldo, Liliana; Vargas, Diana Paola; Moreno-Piraján, Juan Carlos (Frontiers in Chemistry, 2020)
The study of CO2 adsorption on adsorbent materials is a current topic of research interest. Although in real operating circumstances, the removal conditions of this gas is carried out at temperatures between 290 and 303 K and 1 Bar of pressure or high pressures, it is useful, as a preliminary approach, to determine CO2 adsorption capacity at 273K and 1 Bar and perform a thermodynamic study of the CO2 adsorption heats on carbonaceous materials prepared by chemical activation from African palm shell with CaCl2 and H3PO4 solutions, later modified with HNO3 and NH4OH, with the aim to establish the influence that these treatments have on the textural and chemical properties of the activated carbons and their relationship with the CO2 adsorption capacity. The carbonaceous materials were characterized by physical adsorption of N2 at 77K, CO2 at 273K, proximate analysis, Boehm titrations and immersion calorimetry in water and benzene. Activated carbons had a BET area between 634 and 865 m2g−1, with a micropore volume between 0.25 and 0.34 cm3g−1. The experimental results indicated that the modification of activated carbon with HNO3 and NH4OH generated a decrease in the surface area and pore volume of the material, as well as an increase in surface groups that favored the adsorption of CO2, which was evidenced by an increase in the adsorption capacity and the heat of adsorption.